PENERAPAN MODEL PROBLEM BASED LEARNING DAN PENGARUHNYA TERHADAP PENINGKATAN HASIL BELAJAR PROGRAM KEAKSARAAN DI PKBM HASANUDDIN INSTITUTE KECAMATAN SANROBONE KABUPATEN TAKALAR - Thamrin, M. Padli (UNIVERSITAS NEGERI MAKASSAR, 2023)
The purpose of this study was to determine whether or not there is an effect of problem based learning on improving the learning outcomes of the literacy program at PKBM Hasanuddin Institute. The design of this study used Pre-Experimental Designs (non-designs) using the form of One-Group Pretest-Posttest Design. Data collection tools used are observation (observations), test instruments, and documentation. The data analysis technique in this study uses descriptive statistical analysis test and paired sample t-test test with the basis of decision making if the value of Sig (2-tailed) > 0.05 then Ho is accepted and Ha is rejected, if the value of Sig (2-tailed) < 0.05 then Ho is rejected and Ha is accepted. where, prior to the paired sample t-test, the data were tested using descriptive statistical analysis tests, and prerequisite tests, namely normality tests and data homogeneity tests. Based on the results of the study, it is known that learning uses a problem based learning model to test descriptive statistical analysis of the stages of implementing the problem based learning model according to 6 respondents, namely 90/90 x 100 = 100% of the specified criteria. This is a continuous value of 100% including the very good category. and the paired sample t-test test in the experimental class obtained a significance value (2-tailed) of 0.000 more than 0.05 so it can be concluded that the value of learning outcomes is significantly different before and after using the problem-based learning model applied. In this case, Ho is rejected and Ha is accepted.